Samples of stone, pea gravel, coarse sand, geotex, soil, cow dung, coco dust, organic fertilizer and mixed fertilizer (RFA/BNG/001) - Brac Nursery (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of only PDF version of drawings.